2002
DOI: 10.1590/s0066-782x2002001300004
|View full text |Cite
|
Sign up to set email alerts
|

Acute myocardial infarction in elderly patients: comparative analysis of the predictors of mortality. The elderly versus the young

Abstract: Elderly patients had more severe acute myocardial infarction and more extensive disease, a lower index of success, and greater in-hospital mortality. Previous infarction, anterior location and male sex were identified as predictors of mortality in the elderly group (GI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
2
0
0
2
Order By: Relevance
“…As shown earlier and confirmed in our study, elderly patients with STEMI were more often female [2,16], with higher rate of mortality in men [21]. Regarding comorbidities, only chronic renal failure significantly correlated with in-hospital mortality in our patients, also consistent with previous studies [3,22].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As shown earlier and confirmed in our study, elderly patients with STEMI were more often female [2,16], with higher rate of mortality in men [21]. Regarding comorbidities, only chronic renal failure significantly correlated with in-hospital mortality in our patients, also consistent with previous studies [3,22].…”
Section: Discussionsupporting
confidence: 92%
“…Regarding comorbidities, only chronic renal failure significantly correlated with in-hospital mortality in our patients, also consistent with previous studies [3,22]. Congestive heart failure is more frequently in older population with IM [16,20,23], and appeared to be an important predictor of poor outcome [7,22] regardless of appropriate therapeutic approach [7], and more elderly patients with STEMI had higher Killip class > 1, including cardiogenic shock, compared to younger patients [16,21,24]. Widimsky at al [25] compare importance of Killip class on the outcome after PPCI in relation to the age of patients, and found that in-hospital mortality of Killip IV patients was 69% (elderly group), 54% (65-74 years, p < 0.001) and 27% (< 65 years, p < 0.001).…”
Section: Discussionsupporting
confidence: 89%
“…L'età sempre più avanzata degli infartuati è dovuta da una parte ad una maggiore sensibilizzazione della popolazione alla correzione dei fattori di rischio quali l'ipertensione, la dislipidemia, il diabete, il fumo, la trombofilia, e dall'altra all'efficacia di interventi farmacologici in questi ultimi tempi sempre più mirati alla prevenzione CV; tutto ciò ha indubbiamente indotto una più lenta evoluzione della malattia arteriosclerotica ed un certo ritardo nella comparsa delle sue manifestazioni cliniche, anche se non sempre ha consentito di evitare l'evento acuto. Nella fase acuta dell'infarto la mortalità aumenta in maniera esponenziale con l'avanzare dell'età, analogo andamento si registra anche a distanza dall'evento [2,3].…”
unclassified
“…È stato analizzato il paradosso dell'efficacia della trombolisi negli anziani e grandi anziani, in cui gli effetti negativi possono superare i benefici [3][4][5][6][7].…”
unclassified